2023
DOI: 10.1088/1402-4896/aceb96
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of MgSnN2 films using a DFT-1/2 approach

Abstract: The thin films of a newly discovered MgSnN$_2$ Pnma phase was studied using a recently developed DFT-1/2 functional. It was showing that the properties of the investigated films closely relate to the thickness. For those films with odd number of layers, the band gaps are accordingly 2.040 eV, 2.102 eV and 2.107 eV for three, five and seven layers, showing an increasing order along with depth. As for those with even number of layers, the band gaps show a reduction from 2.488 eV for double layer to 2.210 eV for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Based on this, thickness-dependent thin films were constructed and studied on their electronic properties. [31,32] In another work, [33] we investigated the behavior of CdSnN 2 under hydrostatic pressure and found that it undergoes a structural transition and a semiconductor-metal transition when pressurized to 14 GPa as well as a metal-semiconductor transition occurring at 20 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, thickness-dependent thin films were constructed and studied on their electronic properties. [31,32] In another work, [33] we investigated the behavior of CdSnN 2 under hydrostatic pressure and found that it undergoes a structural transition and a semiconductor-metal transition when pressurized to 14 GPa as well as a metal-semiconductor transition occurring at 20 GPa.…”
Section: Introductionmentioning
confidence: 99%